Aenigmachanna mahabali, a new species of troglophilic snakehead (Pisces: Channidae) from Kerala, India - Kumar, Rahul G; Basheer, V.s.; Ravi, Charan (Zootaxa, 2019)
Aenigmachanna mahabali, a new species of troglophilic snakehead is described on the basis of a single specimen recovered from a well in Kerala, India, over 200km south of the type locality for the only known species in the genus. The new species can be distinguished from its congener in possessing fewer dorsal fin rays (53 vs 56-57), fewer total vertebrae (61 vs 64), fewer scales in lateral series (76 vs 83-85) and in the pectoral-fin rays being extended beyond the margin of the membrane into filaments.